SPATIAL DISTRIBUTION AND ACCESSIBILITY OF PUBLIC SECONDARY SCHOOLS IN SOKOTO METROPOLIS: IMPLICATIONS FOR EDUCATIONAL EQUITY AND URBAN PLANNING (FUDMA JOURNAL OF SCIENCES, 2025)
This study investigated the spatial distribution and accessibility of public secondary schools in Sokoto Metropolis, highlighting the implications for educational equity and urban planning. A mixed-method approach was applied to examine patterns and coverage of 88 schools. Location data were obtained using Garmin-60 GPS and Public Secondary School records from the Ministry of Education, Sokoto, and analyzed using Average Nearest Neighbor (ANN) analysis and buffer techniques in ArcGIS. The findings reveal a predominantly clustered distribution of schools across the metropolis, with an ANN ratio of 0.586767, a z-score of -7.331199, and a p-value < 0.001, indicating significant clustering in central urban areas, particularly Sokoto North and South LGAs. Conversely, peripheral regions, such as Wamakko and Kware LGAs, exhibit sparse school distribution and isolated buffer zones, suggesting reduced accessibility for students in these areas. A 2-kilometer buffer analysis shows disparities, with overlapping zones in central areas enhancing accessibility, while peripheral regions face limited school proximity. LGA-specific analyses reveal random distribution patterns in Sokoto North (ANN ratio 1.152340) and Sokoto South (ANN ratio 1.144023), ensuring moderate accessibility but with gaps in peripheral regions. Wamakko LGA exhibits some clustering near urban zones, but fewer schools are found in less populated areas, highlighting geographical and demographic challenges. The study emphasizes the importance of equitable school distribution, with a particular focus on peripheral areas to bridge accessibility gaps. These findings inform policies aimed at improving educational equity and guiding sustainable urban planning in Sokoto Metropolis.
Keywords: Accessibility; Planning; Public Secondary Schools; Spatial